Intrapelvic migration of the hip screw of a proximal femoral nail: report of two cases and review of the literature - Abdalla, Mazen A.; Oikonomou, Leon T.; Giannikas, Konstantinos A. (International Journal of Research in Orthopaedics, 2020)
Two cases of medial migration of the hip screw in cases of cephalon-medullary nailing for the treatment of extra-articular proximal femoral fractures are reported. The first case was revised to hemiarthroplasty, that was subsequently complicated with infection and death of the patient, while the second was revised to a similar devise with favorable outcome. A review of the literature is performed in order to identify the contributing factors that result in the medial migration of the hip screw. Emphasis is given in further reporting of similar cases in order to abolish this potentially lethal complication.